1991
DOI: 10.2165/00003495-199142030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ifosfamide/Mesna

Abstract: Ifosfamide is an oxazaphosphorine alkylating agent with a broad spectrum of antineoplastic activity. It is a prodrug metabolised in the liver by cytochrome P450 mixed-function oxidase enzymes to isofosforamide mustard, the active alkylating compound. Mesna, a uroprotective thiol agent, is routinely administered concomitantly with ifosfamide, and has almost eliminated ifosfamide-induced haemorrhagic cystitis and has reduced nephron toxicity. Therapeutic studies, mostly noncomparative in nature, have demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(24 citation statements)
references
References 172 publications
0
24
0
Order By: Relevance
“…Renal tubular epithelial cells reconvert dimesna to mesna by means of glutathione reductase. Due to their hydrophilic characteristics, both mesna and dimesna are unable to enter the cells (with the exception of the renal tubular and intestinal ones) so that they do not interfere with antineoplastic activity of IFO [43]. Mesna should be given concomitantly with and after IFO because of its short half-life.…”
Section: Toxicitymentioning
confidence: 99%
“…Renal tubular epithelial cells reconvert dimesna to mesna by means of glutathione reductase. Due to their hydrophilic characteristics, both mesna and dimesna are unable to enter the cells (with the exception of the renal tubular and intestinal ones) so that they do not interfere with antineoplastic activity of IFO [43]. Mesna should be given concomitantly with and after IFO because of its short half-life.…”
Section: Toxicitymentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6)(7)(8) Previous studies have confirmed that Mesna does not react with Ifosfamide, obstruct the tumour response to treatment or enter the cancer cells at all. This could be due to its hydrophilic properties, which prevents it from passing through the lipid biological membranes.…”
Section: Introductionmentioning
confidence: 98%
“…(1,(11)(12)(13) Upon entering the bloodstream, Mesna is oxidised to form its less active dimer Dimesna (dithiobis-mercaptoethanesulphonate). (1,2) Similarly to Mesna, Dimesna is a hydrophilic compound which does not transfer across the lipid biological membrane through passive diffusion. (14) Upon reaching the kidneys, Dimesna is reduced back to Mesna and rapidly excreted due to its high solubility in water.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Ifosfamide (3-(2-chloroethyl)-2-[(2-chloroethyl)-amino] tetrahydro-2H-1,3,2-oxazaphosphorin-2-oxide) is a prodrug which is metabolized in the liver by hepatic cytochrome P450 (CYP)-catalyzed 4-hydroxylation to produce the active DNAalkylating agent isophosphoramide mustard (IPM). 5 It is approved for the treatment of testicular cancer 6 and also used as a treatment for a variety of other cancers, including breast cancer, lymphoma, soft tissue sarcoma, osteosarcoma, bone tumor, lung cancer, cervical cancer, and ovarian cancer. 5 The main acute side effects of ifosfamide include those commonly seen with other antineoplastic agents such as neutropenia, thrombocytopenia, nausea and vomiting, alopecia, and hypersensitivity reactions.…”
Section: Introductionmentioning
confidence: 99%